Letter from Carl D. Duncan to Patricia Whiting, November 29, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan recalls attending a lecture presented by the Audubon Scociety and hosted by Dee Jay Nelson. Duncan expresses an apology for a misunderstanding between himself and Whiting and includes a short original poem.